What helps the helpers? Resilience and risk factors for general and profession-specific mental health problems in psychotherapists during the COVID-19 pandemic - Zerban, Matthias; Puhlmann, Lara Marie Christine; Lassri, Dana; Fonagy, Peter; Montague, P. Read; Kiselnikova, Natalia; Lorenzini, Nicolas; Desatnik, Alex; Kalisch, Raffael; Nolte, Tobias (Frontiers in Psychology, 2023)
Introduction Although the COVID-19 pandemic has severely affected wellbeing of at-risk groups, most research on resilience employed convenience samples. We investigated psychosocial resilience and risk factors (RFs) for the wellbeing of psychotherapists and other mental health practitioners, an under-researched population that provides essential support for other at-risk groups and was uniquely burdened by the pandemic. Method We examined 18 psychosocial factors for their association with resilience, of which four were chosen due to their likely relevance specifically for therapists, in a cross-sectional multi-national sample (N = 569) surveyed between June and September 2020. Resilience was operationalized dimensionally and outcome-based as lower stressor reactivity (SR), meaning fewer mental health problems than predicted given a participant’s levels of stressor exposure. General SR (SRG) scores expressed reactivity in terms of general internalizing problems, while profession-specific SR (SRS) scores expressed reactivity in terms of burnout and secondary trauma, typical problems of mental health practitioners. Results Factors previously identified as RFs in other populations, including perceived social support, optimism and self-compassion, were almost all significant in the study population (SRG: 18/18 RFs, absolute βs = 0.16–0.40; SRS: 15/18 RFs, absolute βs = 0.19–0.39 all Ps < 0.001). Compassion satisfaction emerged as uniquely relevant for mental health practitioners in regularized regression. Discussion Our work identifies psychosocial RFs for mental health practitioners’ wellbeing during crisis. Most identified factors are general, in that they are associated with resilience to a wider range of mental health problems, and global, in that they have also been observed in other populations and stressor constellations.